HSD17B13: A Potential Therapeutic Target for NAFLD - Zhang, Hai-bo; Su, Wen; Xu, Hu; Zhang, Xiao-yan; Guan, You-fei (Frontiers in Molecular Biosciences, 2022)
Nonalcoholic fatty liver disease (NAFLD), especially in its inflammatory form (steatohepatitis, NASH), is closely related to the pathogenesis of chronic liver disease. Despite substantial advances in the management of NAFLD/NASH in recent years, there are currently no efficacious therapies for its treatment. The biogenesis and expansion of lipid droplets (LDs) are critical pathophysiological processes in the development of NAFLD/NASH. In the past decade, increasing evidence has demonstrated that lipid droplet-associated proteins may represent potential therapeutic targets for the treatment of NAFLD/NASH given the critical role they play in regulating the biogenesis and metabolism of lipid droplets. Recently, HSD17B13, a newly identified liver-enriched, hepatocyte-specific, lipid droplet-associated protein, has been reported to be strongly associated with the development and progression of NAFLD/NASH in both mice and humans. Notably, human genetic studies have repeatedly reported a robust association of HSD17B13 single nucleotide polymorphisms (SNPs) with the occurrence and severity of NAFLD/NASH and other chronic liver diseases (CLDs). Here we briefly overview the discovery, tissue distribution, and subcellular localization of HSD17B13 and highlight the important role in promoting the pathogenesis of NAFLD/NASH in both experimental animal models and patients. We also discuss the potential of HSD17B13 as a promising target for the development of novel therapeutic agents for NAFLD/NASH.